2020
DOI: 10.31849/elsya.v2i1.3631
|View full text |Cite
|
Sign up to set email alerts
|

"Bits and Pieces" to Improve the Students' Writing Skill: Using Educational Game as an Approach to Teach Descriptive Text

Abstract: Students in Indonesia who learn English as a Foreign Language (EFL) encounter problems in learning how to write in English. Not a novel problem in the least, but the more connected the world is becoming due to the availability of information and communication technologies (ICT). This study aims to address the need to improve the generation’s English skills, lest they are left behind the moving era. This study is a classroom action research (CAR), using a test, observation, field note, and interviews as the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 10 publications
(10 reference statements)
0
10
0
Order By: Relevance
“…Additionally, The Bits and Pieces game found out that it could be an alternative to develop students writing skills in some aspects, for instance; like content and organization. The result was supported by Andayani (2018) and Rizky (2020).…”
Section: The Effect Between the Use Of The Bits And Pieces Game And The Conventional Teaching Methods Towards Students' Achievement On Wrmentioning
confidence: 54%
See 1 more Smart Citation
“…Additionally, The Bits and Pieces game found out that it could be an alternative to develop students writing skills in some aspects, for instance; like content and organization. The result was supported by Andayani (2018) and Rizky (2020).…”
Section: The Effect Between the Use Of The Bits And Pieces Game And The Conventional Teaching Methods Towards Students' Achievement On Wrmentioning
confidence: 54%
“…Writing requires one's ability to express ideas, opinions, thoughts, and feeling to be good at writing to understand the written topic. This skill is also notoriously one of the most challenging skills for EFL students to master (Rizky, 2020). Jimmi (2017) added that writing skills are of course, very important in the process of learning English because writing is one of the skills besides reading, speaking, and listening.…”
Section: Introductionmentioning
confidence: 99%
“…pastime and the approach facilitates them to realize the textual content. Moreover, a previous research conducted byDanang (2018);Junavia & Astuti (2021);Kristiani et al, (2021) &Rizky (2020) found out that the students' reaction to mastering English via the usage of the Frontloading have been very positive, and the Frontloading have beencapable affects students' to know and comprehending the which means of surprising phrases every cycle. After that, a quasi-experimental research performed by Windiati et al, (2018); Tisma (2021) & Zuhriyah (2020) concluded that the Frontloading strategy is relevant to put in force in coaching studying for students and its impacts affect the students' comprehension.…”
mentioning
confidence: 94%
“…Therefore, Santika & Herdi (2020) state that descriptive text affords brilliant information of ways a person seems and specifically it can be used to describe thing(s) or person(s). Also, Rizky (2020) states that the teacher has to present a clean and energetic description relies upon on a near item and for the reason that descriptive textual content has language features, for example identity and description, it's far vital for the trainer to CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan Vol.2, No.4 NOVEMBER 2022e-ISSN: 2961p-ISSN: 2962-3561, Hal 193-204 be innovative and creative. In order to draw students' attention, the teacher must be greater selective in selecting the fabric that's primarily based totally on the students' want and hobby to make the system of coaching and mastering vocabulary be greater fun.…”
Section: Introductionmentioning
confidence: 99%
“…Game is one of interesting instrument that used to attract students' to follow the teaching and learning process. Games are associated with a feeling of happiness (Rizky, 2020). For this reason, most learners appreciate games even if they are not familiar with the rules.…”
Section: Introductionmentioning
confidence: 99%